2014
DOI: 10.3926/jiem.1150
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic framework and health check tool for engineering and technology projects

Abstract: Purpose: Development of a practitioner oriented diagnostic framework and health check tool to support the robust assessment of engineering and technology projects. Design/methodology/approach: The research is based on a literature review that draws together insights on project assessment and critical success factors to establish an integrated systems view of projects. This is extended to allow a comprehensive diagnostic framework to be developed along with a high-level health check tool that can be readily dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The purpose of the Periodic project health check reports (PHC) tool is to systematically specify how project variables are handled to ascertain whether a project is managed systemically (as in a healthy project) or randomly (in the case of a troubled project). The health check tool offers an illustrative view of the situation faced by the project manager in the troubling case and highlights how corrective steps were taken in focused areas to support the recovery of the projects (Jaafari, 2007;Philbin and Kennedy, 2014). Project health reports help project managers to identify the root causes of any issues early in the project delivery process and to enable managers to maintain overall project performance better (Almahmoud et al, 2012).…”
Section: Project Health Checks (Phc)mentioning
confidence: 99%
“…The purpose of the Periodic project health check reports (PHC) tool is to systematically specify how project variables are handled to ascertain whether a project is managed systemically (as in a healthy project) or randomly (in the case of a troubled project). The health check tool offers an illustrative view of the situation faced by the project manager in the troubling case and highlights how corrective steps were taken in focused areas to support the recovery of the projects (Jaafari, 2007;Philbin and Kennedy, 2014). Project health reports help project managers to identify the root causes of any issues early in the project delivery process and to enable managers to maintain overall project performance better (Almahmoud et al, 2012).…”
Section: Project Health Checks (Phc)mentioning
confidence: 99%
“…While this figure was later challenged by Glass (2006), recent survey data still paints a gloomy picture; unfortunately, 45% of all large IT projects (with an initial budget exceeding US $15 million) experience budget overruns, 7% run overtime, and deliver 56% less value than envisaged (Bloch et al, 2012). Various approaches have been explored in order to help improve project success, such as the adoption of a broader (i.e., systemic) perspective of project outcomes (Shenhar and Dvir, 2007) as well as the development of a diagnostic framework and health check tool for engineering and technology project (Philbin and Kennedy, 2014).…”
Section: Low Levels Of Project Successmentioning
confidence: 99%
“…Researchers have explored this area from a theoretical perspective, for instance, investigating the relationship between construction project management theory and transaction cost economics (Walker and Kwong Wing, 1999). Other researchers have assessed how to improve the performance of the earned value analysis technique as a construction project management tool (Howes, 2000) and the development of a diagnostic framework and health check tool for engineering and technology projects (Philbin and Kennedy, 2014). Although it has also been reported that this sector faces a number of major challenges associated with managing projects as identified by Wilkinson (2001), where many of the fundamental problems associated with managing construction projects were found to be relationship-based.…”
Section: Introductionmentioning
confidence: 99%